(untitled) (Research, Society and Development, 2021)
Objective: To analyze the avoidability of infant and fetal deaths and the quality of research as indicators of iniquity in a medium-sized municipality in Brazil. Method: This is a documentary and quantitative study, with analysis of secondary data from the Mortality Information System (SIM) for the municipality of Caicó, in Rio Grande do Norte, reported in the period 2010 to 2015, with investigation of 58 infant deaths and fetal. SIM data were compared with data from the municipality’s Mortality Committee based on the death certificate. Results: A low investigation of cases was identified (45.3%). Preventable deaths predominated (64.8%), evidenced by preventable deaths, if adequate attention was given to women during childbirth. There was a high degree of disagreement between the evaluation made in this study and the municipal investigation: fetal deaths, five cases (29.4%) presented agreement and, of infant deaths, only two (12.5%) Cases. Conclusion: There are weaknesses in the surveillance of death and in the performance of the municipal mortality committee. It is necessary to recognize the relevance of the investigation to the knowledge of these deaths as a tool to reduce health inequities.